Synergistic impact of invasive alien plants and the alien Argentine ant on local ant assemblages in the Western Cape - Schoeman, Colin Stefan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2008.